2020
DOI: 10.1155/2020/9624927
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Prediction of Pavement Settlement Caused by Jacking Construction of Ultra-Shallow Rectangular Shield Frame Bridge

Abstract: The primary purpose of this paper is to analyze and predict the ground settlement law of large-span rectangular shield frame bridge jacking project, to provide a reference for the optimization design and safe construction of similar projects. In this paper, combined with the jacking project of ultra-shallow buried soft soil layer rectangular shield frame bridge, through the on-site monitoring, the settlement deformation law of the longitudinal and transverse sections of the expressway pavement during the jacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It is assumed that the regionalized variables are not independent of each other, have absolute randomness and structural characteristics, and satisfy the second-order stationary and intrinsic stationary conditions. Simultaneously, the Kriging method [44,45] considers the spatial correlation property of the description object in the process of data gridding, which makes the interpolation result more scientifc and closer to the actual situation. It can give the interpolation error (Kriging variance) so that the interpolation's reliability is clear at a glance.…”
Section: Kriging Filtering Algorithmmentioning
confidence: 99%
“…It is assumed that the regionalized variables are not independent of each other, have absolute randomness and structural characteristics, and satisfy the second-order stationary and intrinsic stationary conditions. Simultaneously, the Kriging method [44,45] considers the spatial correlation property of the description object in the process of data gridding, which makes the interpolation result more scientifc and closer to the actual situation. It can give the interpolation error (Kriging variance) so that the interpolation's reliability is clear at a glance.…”
Section: Kriging Filtering Algorithmmentioning
confidence: 99%
“…Bridge construction methods can be divided into many types, including cantilever construction (basket construction method), support construction, hoisting construction, jacking construction method, rotation construction, etc [1][2][3]. Bridge construction methods are usually chosen based on factors such as local topography, bridge usage, and construction costs.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the relationship between the vertical displacement difference of asynchronous bridge jacking and the deformation behavior of the girders. Hu Danyi [9], based on a rectangular shield bridge jacking project in an ultra-shallow soft soil layer, reported that the fundamental law of pavement settlement over time was summarized by the monitoring data of the on-site test section.…”
Section: Introductionmentioning
confidence: 99%